Involvement of STAT5 in Oncogenesis - Clarissa Esmeralda Halim; Shuo Deng; Mei Shan Ong; Celestial T. Yap (Biomedicines, 2020)
Signal transducer and activator of transcription (STAT) proteins, and in particular STAT3, have been established as heavily implicated in cancer. Recently, the involvement of STAT5 signalling in the pathology of cancer has been shown to be of increasing importance. STAT5 plays a crucial role in the development of the mammary gland and the homeostasis of the immune system. However, in various cancers, aberrant STAT5 signalling promotes the expression of target genes, such as cyclin D, Bcl-2 and MMP-2, that result in increased cell proliferation, survival and metastasis. To target constitutive STAT5 signalling in cancers, there are several STAT5 inhibitors that can prevent STAT5 phosphorylation, dimerisation, or its transcriptional activity. Tyrosine kinase inhibitors (TKIs) that target molecules upstream of STAT5 could also be utilised. Consequently, since STAT5 contributes to tumour aggressiveness and cancer progression, inhibiting STAT5 constitutive activation in cancers that rely on its signalling makes for a promising targeted treatment option.